2002
DOI: 10.1002/hipo.10035
|View full text |Cite
|
Sign up to set email alerts
|

BDNF–triggered events in the rat hippocampus are required for both short‐ and long‐term memory formation

Abstract: Information storage in the brain is a temporally graded process involving different memory types or phases. It has been assumed for over a century that one or more short-term memory (STM) processes are involved in processing new information while long-term memory (LTM) is being formed. Because brain-derived neutrophic factor (BDNF) modulates both short-term synaptic function and activity-dependent synaptic plasticity in the adult hippocampus, we examined the role of BDNF in STM and LTM formation of a hippocamp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
201
2
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 306 publications
(214 citation statements)
references
References 81 publications
6
201
2
2
Order By: Relevance
“…In particular, we have found BDNF to be maximally induced 2 h following contextual fear conditioning (Barrientos et al, 2004) and Alonso et al (2002) has shown that BDNF is necessary for at least 4 h after training to form a long-term memory. Since PGE 2 reduces post-conditioning BDNF mRNA at 2 h, it is likely that this may be a mechanism for PGE 2 's memory impairing effects.…”
Section: Discussionmentioning
confidence: 91%
“…In particular, we have found BDNF to be maximally induced 2 h following contextual fear conditioning (Barrientos et al, 2004) and Alonso et al (2002) has shown that BDNF is necessary for at least 4 h after training to form a long-term memory. Since PGE 2 reduces post-conditioning BDNF mRNA at 2 h, it is likely that this may be a mechanism for PGE 2 's memory impairing effects.…”
Section: Discussionmentioning
confidence: 91%
“…Further support for the involvement of BDNF in the one-trial avoidance task is provided by the observation that the infusion of exogenous BDNF into the CA1 region facilitates short-term memory retention scores ( Fig. 4A; Alonso et al 2002). In additional experiments, not only did BDNF infusion elicit a rapid increase in p-ERK, but the infusion of anti-BDNF antibody decreased p-ERK (Alonso et al 2002).…”
Section: Bdnf and Memory Consolidationmentioning
confidence: 83%
“…Because of the involvement of the MAPK pathway in memory formation and synaptic plasticity (for review, see Sweatt 2001), and combined with the findings previously discussed regarding BDNF-LTP, this pathway seems a likely target for investigations examining the effect of BDNF in behavioral learning paradigms. In fact, recent work by Alonso et al (2002) shows the requirement of BDNF in the formation of both short-and long-term memory involving ERK-dependent and -independent mechanisms. Alonso et al (2002) show that BDNF signaling via ERK1/2 is required in a hippocampal-dependent one-trial avoidance learning paradigm in rats.…”
Section: Bdnf and Memory Consolidationmentioning
confidence: 99%
See 1 more Smart Citation
“…BDNF, acting at TrkB receptors, has been implicated in LTP induction 272,273 and fear acquisition [274][275][276] Recently, Chhatwal et al 277 found evidence for a role of BDNF in fear extinction as well. These investigators reported a time-dependent upregulation of BDNF exon Vcontaining mRNA within the BLA in extinguished rats relative to nonextinguished controls.…”
Section: Neurotransmitter Systemsmentioning
confidence: 99%